Phenotyping common beans for adaptation to drought: protocol for greenhouse evaluation - Polanía Perdomo, José A.; Rivera, M.; Ricaurte, Jaumer; Rao, Idupulapati M. (2012)
This protocol was provided for the identification of phenotypic differences in drought resistance in common beans (Phaseolus vulgaris L.). It is available in both PDF and photo gallery format with the aim of providing visiting students and researchers with a consultation document they can use to answer questions about our in-house methodologies.